2006
DOI: 10.1016/j.worlddev.2005.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Globalization, Forest Resurgence, and Environmental Politics in El Salvador

Abstract: El Salvador is often seen as a classic environmental "basket case" of population growth, deforestation and collapsing biodiversity. This view, which was open to question even when it was first articulated (cf. Durham 1972) is not supported by contemporary studies. Today, El Salvador is experiencing a resurgence in forest cover. The changing national and international context suggests that globalization, while clearly triggering deforestation in many places in Latin America, can also stimulate forest resurgence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
155
0
8

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(166 citation statements)
references
References 34 publications
3
155
0
8
Order By: Relevance
“…However, we argue that the industrialization process was only the initial economic trigger and that the present drivers of forest recovery reflect general processes at work in other tropical regions undergoing development (Grau et al 2003). Moreover, foreign actors and 4y Springer globalization are playing an increasingly important role in forest cover change in many tropical regions by driving demand for agricultural products and labor (Hecht et al 2006;Perz 2007). Therefore, understanding the role that socioeconomic drivers have on forest recovery relative to biophysical and landscape variables is critical to land use planning and maximization of the ecosystem services secondary forests provide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we argue that the industrialization process was only the initial economic trigger and that the present drivers of forest recovery reflect general processes at work in other tropical regions undergoing development (Grau et al 2003). Moreover, foreign actors and 4y Springer globalization are playing an increasingly important role in forest cover change in many tropical regions by driving demand for agricultural products and labor (Hecht et al 2006;Perz 2007). Therefore, understanding the role that socioeconomic drivers have on forest recovery relative to biophysical and landscape variables is critical to land use planning and maximization of the ecosystem services secondary forests provide.…”
Section: Discussionmentioning
confidence: 99%
“…Although much of the focus of research on land use change in the tropics has been on deforestation, socioeconomic changes and abandonment of agricultural land and pastures have led to an increase in secondary forest cover in many tropical regions (Franco et al 1997;Rudel et al 2000;Chang and Tsai 2002;Klooster 2003;Read et al 2003;Hecht et al 2006). The extent of secondary forests in the tropics was recently estimated at 850 million hectares (ITTO 2002).These secondary forests provide many of the services 4y Springer attributed to primary forests including regulation of water quality and flow, erosion control, carbon sequestration, restoration of nutrients and soil properties in former agricultural lands, biodiversity conservation, and enhanced connectivity of fragmented landscapes (ITTO 2002;Chazdon 2003).…”
Section: Introductionmentioning
confidence: 99%
“…DCs are particularly vulnerable given their lack of resources to mitigate these consequences. Proponents of globalisation, such as the WTO, claim that its policies encourage environmental improvement but their statistical justifications may apply only where 'weak conditions' are satisfied, or when limited environment metrics are used (Hecht et al, 2006).…”
Section: Social and Environmental Accountabilitymentioning
confidence: 99%
“…In tropical developing El Salvador, a survey that encompassed secondary growth, pasture successions, living fences, tenure demarcations, urban forests, and orchards revealed that land with Ͼ25% tree cover expanded from 72% to 93% between 1992 and 2001 (12). Forests are recovering in Puerto Rico and the Dominican Republic, next to deforested Haiti (13).…”
Section: Carbon Concentration Tons͞tonmentioning
confidence: 99%